Direct Observation of Confinement Effects of Semiconducting Polymers in Polymer Blend Electronic Systems. Issue 14 (14th May 2021) - Park, Byoungwook; Kang, Hongkyu; Ha, Yeon Hee; Kim, Jehan; Lee, Jong‐Hoon; Yu, Kilho; Kwon, Sooncheol; Jang, Soo‐Young; Kim, Seok; Jeong, Soyeong; Hong, Soonil; Byun, Seunghwan; et al.
Abstract: The advent of special types of polymeric semiconductors, known as "polymer blends, " presents new opportunities for the development of next‐generation electronics based on these semiconductors' versatile functionalities in device applications. Although these polymer blends contain semiconducting polymers (SPs) mixed with a considerably high content of insulating polymers, few of these blends unexpectedly yield much higher charge carrier mobilities than those of pure SPs. However, the origin of such an enhancement has remained unclear owing to a lack of cases exhibiting definite improvements in charge carrier mobility, and the limited knowledge concerning the underlying mechanism thereof. In this study, the morphological changes and internal nanostructures of polymer blends based on various SP types with different intermolecular interactions in an insulating polystyrene matrix are investigated. Through this investigation, the physical confinement of donor–acceptor type SP chains in a continuous nanoscale network structure surrounded by polystyrenes is shown to induce structural ordering with more straight edge‐on stacked SP chains. Hereby, high‐performance and transparent organic field‐effect transistors with a hole mobility of ≈5.4 cm 2 V –1 s –1 and an average transmittance exceeding 72% in the visible range are achieved. Abstract : The confinement effect of semiconducting polymer (SP) is a core factor directly influencing the charge transport properties of polymer blend electronic systems. This study generalizes that the physical confinement of donor–acceptor type SP can induce continuously connected SP network in insulating polymer matrix and the structural ordering with more straight edge‐on stacked SP chains enable an efficient charge transport.